PENINGKATAN KAPASITAS PRODUKSI PETI ALUMUNIUM UNTUK MEMENUHI KEBUTUHAN PERMINTAAN MELALUI OPTIMALISASI JADWAL INDUK PRODUKSI DI PT. BJK - Harini, - (Lembaga Layanan Pendidikan Tinggi Wilayah III Jakarta, 2014)
PT. BJK which is a manufacturing company that produces operational vehicles such as cars crates, garbage trucks and so forth. Production planning is expected to meet the master production schedule specified in other words, can meet the market demand in the PT. BJK. Often there is excess stock products when demand for goods is reduced while on a sat high demand, companies have difficulties to meet the existing demand. The purpose of this study is: (1) the master production schedule and analyze the results of the master production schedule. (2) The master production schedule that has been repaired is expected to minimize the product, so in accordance with the needs and desires of the company. The method used is based on measurements and literature. The conclusion is (1) Optimization of the master production schedule can be achieved by using the method of permanent workers because it can meet the production demand of 147 units / month. Earlier the company was only able to meet the production demand of 120 units / month. (2) master production scheduling model that suits your needs is to use the method of permanent workers. This ni due to the cost of production using these methods required very few of the other methods is Rp. 644.459.500,-.